2017
DOI: 10.18632/oncotarget.14696
|View full text |Cite
|
Sign up to set email alerts
|

Piwil2-transfected human fibroblasts are cancer stem cell-like and genetically unstable

Abstract: Uncontrolled cell proliferation and inhibition of apoptosis are considered to be vital for cancer initiation, maintenance, infiltration, metastasis and recurrence after anti-cancer therapy. Here we report the generation of a novel cell line by reprogramming child foreskin fibroblast with the full length apoptosis inhibitor gene PIWIL2. The fibroblasts transfected with PIWIL2 expressed the stem cell markers OCT-4, NANOG, SOX-2, KLF-4 and C-MYC; endoderm marker AFP and GATA6; mesoderm markers ACTA2 and BRACHYURY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…PIWIL-2 expression has been shown to be associated with stem cell properties and has been regarded as a potential neoplasia biomarker [41,42,53]. Intriguingly, we could demonstrate that in adult skin, PIWIL-2 is not predominantly expressed in compartments with possible stem cell populations in the epidermis.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…PIWIL-2 expression has been shown to be associated with stem cell properties and has been regarded as a potential neoplasia biomarker [41,42,53]. Intriguingly, we could demonstrate that in adult skin, PIWIL-2 is not predominantly expressed in compartments with possible stem cell populations in the epidermis.…”
Section: Discussionmentioning
confidence: 47%
“…An essential role of miRNAs and long non-coding RNAs in skin wound healing [ 17 ] and differentiation [ 30 , 51 ] has been revealed recently, but a possible role of piRNAs in the skin has not yet been shown. Since PIWIL-2 is known to play a role in the maintenance of germline stem cells as well as in the development of carcinomas [ 27 , 53 ], we set out to look for a possible role of this protein and piRNAs in the skin. We investigated the expression pattern and possible association of PIWIL-2 with epithelial stem cell compartments and neoplasias.…”
Section: Introductionmentioning
confidence: 99%
“…FBs, fibroblasts; Piwil2-iCSC-Exo, exosomes derived from Piwil2-induced cancer stem cells. transfected with the self-renewing gene Piwil2 (36), that served as a CSC model for in vitro experiments. Using this model, it was demonstrated that Piwil2-iCSC-Exo enhance the proliferation, migration and invasion of FBs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines and cell culture. Piwil2-iCSCs and FBs were obtained from the Chongqing Key Laboratory of Child Urogenital Development and Tissue Engineering (36). The Piwil2-iCSCs were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with penicillin/streptomycin and 10% fetal bovine serum (FBS; Gibco; Thermo Fisher Scientific) depleted of bovine exosomes by overnight ultracentrifugation at 100,000 x g, followed by filtration through a 0.2-µm filter (Millipore).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation